2021
DOI: 10.1088/1741-2552/ac0f4b
|View full text |Cite
|
Sign up to set email alerts
|

Interpretable deep learning as a means for decrypting disease signature in multiple sclerosis

Abstract: Objective. The mechanisms driving multiple sclerosis (MS) are still largely unknown, calling for new methods allowing to detect and characterize tissue degeneration since the early stages of the disease. Our aim is to decrypt the microstructural signatures of the Primary Progressive versus the Relapsing-Remitting state of disease based on diffusion and structural magnetic resonance imaging data. Approach. A selection of microstructural descriptors, based on the 3D-Simple Harmonics Oscillator Based Reconstructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…One of the strengths of ML models is the capability to capture hidden relationships among complex multi-dimensional data. They have been explored for several tasks, inter-alia, disease classification [1][2][3] , human body segmentation [4][5][6][7] , the definition of diagnostic scores 8 , drug-discovery 9,10 and data augmentation through the generation of synthetic samples [11][12][13][14] . Despite most of these examples leveraging medical images as the preferred data format, a variety of data types are collected by hospitals, clinical laboratories, and other healthcare institutions.…”
Section: Introductionmentioning
confidence: 99%
“…One of the strengths of ML models is the capability to capture hidden relationships among complex multi-dimensional data. They have been explored for several tasks, inter-alia, disease classification [1][2][3] , human body segmentation [4][5][6][7] , the definition of diagnostic scores 8 , drug-discovery 9,10 and data augmentation through the generation of synthetic samples [11][12][13][14] . Despite most of these examples leveraging medical images as the preferred data format, a variety of data types are collected by hospitals, clinical laboratories, and other healthcare institutions.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most exploited methods are those relying on heatmaps revealing which parts of the input played a relevant role in determining the output. An example of a comprehensive solution was proposed in [10], where LRP was used to interpret the results of a patient stratification task aiming at distinguishing two multiple sclerosis phenotypes (progressive versus relapsing-remissing) and validation included the assessment of the role of confounds on the classification outcomes as well as association studies of LPR maps with microstructural descriptors that were previously shown to be significantly different in the two phenotypes of disease. Another example is [11] where the objective was to contrast feature-based and example-based explainable AI techniques using the Heart Disease Dataset from UCI (https://www.kaggle.com/cherngs/ heart-disease-clevelanduci) to highlight the respective pros and cons.…”
Section: Biomedical Datamentioning
confidence: 99%
“…However, the use of DL techniques to predict disease progression is still largely unexplored. Some recent studies have presented promising results for future prediction of disability ( Roca et al, 2020 , Storelli et al, 2022 , Tousignant et al, 2019 ) and cross-sectional patient stratification ( Cruciani et al, 2021 , Marzullo et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…New tendencies in the field have also put emphasis on producing explainable DL-based techniques, with the goal of disentangling the reason behind DL decisions, therefore providing additional information that could be extremely useful to the end users enhancing data insights ( Bach et al, 2015 , Simonyan et al, 2013 , Springenberg et al, 2014 ). This task of deciphering the “black box” of DL-based models in MS has recently been studied for disease diagnosis ( Eitel et al, 2019 , Lopatina et al, 2020 ) and MS phenotype signature decrypting ( Cruciani et al, 2021 ). All these studies concluded that the use of the layer-wise relevance propagation (LRP)( Bach et al, 2015 ), among other (similar) methods, is the most promising tool for these analyses providing individual heatmaps for each subject, called attention maps, reflecting the voxel-specific relevance to the classification output, according to the DL model, in an easy and intuitive way.…”
Section: Introductionmentioning
confidence: 99%